Relationship between Some Properties of Marls and Different Types of Erosions in Talkhe-rood Watershed - Salmasi Ramin; Abbas Ahmadi (جغرافیا و پایداری محیط)
The soil erosion and sediment yield are mainly due to marl formations in the Talkherood watershed. This study was conducted to evaluate relationship between physicochemical properties of Talkhe_rood watershed marl samples and rill, gully, mass and badland erosion types. For this purpose, marl samples were taken from marl sediment of homogenous work units. Twenty four samples were selected, and some of main physicochemical properties of these marls were determined in lab. These properties were: pH, EC, CEC, Lime, gypsum and OC contents, SAR, Na, K, Cl and Ca + Mg and clay, silt and sand percentages. These data were interpreted by ANOVA and mean comparisons analyze (SPSS software Ver. 11.5) methods. Results showed that pH, gypsum content and sand percentage had statistically significant differences between four erosion types. Mean comparison showed that significant difference of pH, was between mass and badland erosions, sand between badland and gully ones, and gypsum, rill and gully, also badland and gully ones.